The Neoconservatives and the Pope: Misreading John Paul II in George Weigel's Biographies - Russell, Jesse B. B. (Political theology, 2019)
With the recent release of his autobiographical narrative of the composition of the papal biography, Witness to Hope, prominent Catholic neoconservative George Weigel has invited a reexamination of the presentation of John Paul II to the world by Catholic neoconservatives. In his biographies, George Weigel crafts an often misleading portrait of Pope John Paul II as the pope of American liberalism and neoconservativism. Ironically, at the same time, the story of Weigel's biographies contains the story of the rise and fall of the Catholic neoconservative movement in America.